2010
DOI: 10.1021/ma100744p
|View full text |Cite
|
Sign up to set email alerts
|

2H NMR and Simulation Studies of Chain Segment Orientation in PDMS Bimodal Networks

Abstract: We present a systematic study through 2H NMR and molecular simulations of chain segment orientation in model PDMS bimodal networks. Estimates of the average segment orientation order parameter in model PDMS bimodal networks compare well to those of equivalent simulated networks. We find that line shapes of short and long chains are different due to the dissimilar degrees of motional restrictions. Short-chain conformations are perturbed from random coiled states when incorporated into bimodal networks whereas l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…The influence of the network topology on the behaviour at large strains has mostly been investigated for unfilled model networks [67][68][69][70][71][72] . It has been shown that to get better elongation and ultimate strength, multi-modal networks were superior to unimodal ones.…”
Section: Behaviour Of Peroxide and Platinum Cured Silicone Elastomersmentioning
confidence: 99%
“…The influence of the network topology on the behaviour at large strains has mostly been investigated for unfilled model networks [67][68][69][70][71][72] . It has been shown that to get better elongation and ultimate strength, multi-modal networks were superior to unimodal ones.…”
Section: Behaviour Of Peroxide and Platinum Cured Silicone Elastomersmentioning
confidence: 99%
“…The same samples were previously investigated by Genesky, Cohen and co-workers, who also published details on their preparation. 24,25…”
Section: A Samplesmentioning
confidence: 99%
“…More realistic network structures with random cross-links were also tried with the probabilistic algorithms, in which the molecules were essentially static and the capture radius for the cross-linking reaction was gradually incremented [4]. Dynamic processes of the bond fluctuation model in Monte Carlo simulations were also used for the reactive cross linking of polymer chains [5][6][7][8][9], while it did not give realistic kinetics of the whole systems.…”
Section: Introductionmentioning
confidence: 99%